A Study to Assess the Effectiveness of Constructed Wetland Technology for Polluted Surface Water Treatment - Cong Manh, Nguyen; Van Minh, Phan; Tri Quang Hung, Nguyen; Thai Son, Phan; Minh Ky, Nguyen (VNU Journal of Science: Earth and Environmental Sciences; Vol 35 No 2DO - 10.25073/2588-1094/vnuees.4372, 2019)
Abstract: The study aims to assess the applying effectiveness of constructed wetland technology for polluted surface water treatment. The experimental models were operated with 2 hydraulic loadings of 500mL/min/m 2 (T1) and 1500mL/min/m 2 (T2). The reed grass ( Phragmites australis ) was selected for the studying process. The surface water resource was removed from the pollutant components (TSS, BOD 5 , COD) and harmful microorganisms (fecal coliform) which aim to protect the water quality and aquatic ecosystems. The results showed the treatment effectiveness of loading of 500mL/min/m 2 is higher than the loading of 1500mL/min/m 2 , especially in the reed planting trial. In particular, the treatment efficiency of pollutants such as TSS, BOD 5 , COD reached a high rate of 85%, 90%, and 87%, respectively. In addition, ANOVA statistical analysis showed the effectiveness of water quality parameters belong to two loadings were statistically significant (P<0.05). Thus, the surface water pollutant removal by subsurface vertical flow constructed wetland technology could be contributed to promoting the sustainable agricultural development. Keywords: Constructed wetland, removal, surface water, Phragmites australis , pollution. References : [1] Z. ElZein, A. Abdou, I.A. ElGawad, Constructed Wetlands as a Sustainable Wastewater Treatment Method in Communities, Procedia Environmental Sciences 34 (2016) 605-617. https://doi.org/10. 1016/ j.proenv.2016.04.053. [2] R.H. Kadlec, S.D. Wallace, Treatment Wetlands, CRC Press/Lewis Pucblishers, Boca Raton, FL, 2009. [3] J. Vymazal, Constructed Wetlands for Wastewater Treatment, Water 2(3) (2010) 530-549. https://doi. org/10.3390/w2030530. [4] L. Volker, E. Elke, L.W. Martina, L. Andreas, M.G. Richard, Nutrient Removal Efficiency and Resource Economics of Vertical Flow and Horizontal Flow Constructed Wetlands, Ecological Engineering 18 (2) (2001) 157-171. https://doi.org/ 10.1016/S0925-8574(01)00075-1. [5] M. Ilda, F. Daniel, P. Enrico, F. Laura, M. Erika, Z. Gabriele, A cost-effectiveness analysis of seminatural wetlands and activated sludge wastewater-treatment systems, Environmental Management 41 (1) (2007) 118-129. https://doi.org /10.1007/s00267-007-9001-6. [6] J. Vymazal, The use of constructed wetlands with horizontal sub-surface flow for various types of wastewater, Ecological Engineering 35 (2009) 1-17. https://doi.org/10.1016/j.ecoleng.2008.08.016. [7] S. Katarzyna, H.G. Magdalena, The use of constructed wetlands for the treatment of industrial wastewater, Journal of Water and Land Development 34 (2017) 233–240. https://doi.org /10.1515/jwld-2017-0058. [8] S. Dallas, B. Scheffe, G. Ho, Reedbeds for greywater treatment-case study in Santa Elena-Monteverde, Costa Rica, Central America. Ecol. Eng. 23 (2004) 55-61. https://doi.org/10.1016/ j.ecoleng.2004.07.002. [9] Tổng cục Thống kê, Niên giám thống kê Việt Nam, NXB Thống kê, Hà Nội, 2018. [10] Bộ Tài nguyên và Môi trường, Báo cáo hiện trạng môi trường quốc gia – Môi trường nước mặt, Hà Nội, 2012. [11] UBND tỉnh Bình Dương, Quyết định số 3613/QĐ-UBND về việc Quy hoạch tài nguyên nước tỉnh Bình Dương giai đoạn 2016 - 2025, tầm nhìn đến năm 2035, Bình Dương, 2016. [12] M. Mirco, T. Attilio, Evapotranspiration from pilot-scale constructed wetlands planted with Phragmites australis in a Mediterranean environment, Journal of Environmental Science and Health 48 (5) (2013) 568-580. https://doi.org/ 10.1080/10934529.2013.730457. [13] K.J. Havens, H. Berquist, W.I. Priest, Common reed grass, Phragmites australis, expansion into constructed wetlands: Are we mortgaging our wetland future? Estuaries 26 (2003) 417-422. https://doi.org/10.1007/BF02823718. [14] S. Aboubacar, R. Mohamed, A. Jamal, A. Omar, E. Samira, Exploitation of Phragmites australis (Reeds) in Filter Basins for the Treatment of Wastewater, Journal of Environmental Science and Technology 11 (2018) 56-67. https://doi.org/10. 3923/jest.2018.56.67. [15] S.I. Abou-Elela, M.S. Hellal, Municipal wastewater treatment using vertical flow constructed wetlands planted with Canna, Phragmites and Cyprus, Ecol. Eng. 47 (2012) 209-213. https://doi.org/10.1016/j. ecoleng.2012.06.044. [16] H. Brix, A.C. Arias, The use of vertical flow constructed welands for on-site treatment of domestic wastewater: New Danish guidelines, Ecological Engineering 25 (2005) 491-500. https://doi.org/10.1016/j.ecoleng.2005.07.009. [17] J. Puigagut, J. Villasenor, J.J. Salas, E. Becares, J. Garcia, Subsurface-flow constructed wetlands in Spain for the sanitation of small communities: A comparison study, Ecological Engineering 30 (2007) 312-319. https://doi.org/10.1016/j.ecoleng. 2007.04.005. [18] R. Kadlec, R. Knight, Treatment Wetlands, CRC Press, 1996. [19] L. Yang, H.T. Chang, M.N.L. Huang, Nutrient removal in gravel-and soil-based wetlands microcosms with and without vegetation, Ecological Engineering 18 (2001) 91-105. https://doi.org/10.1016/S0925-8574(01)00068-4. [20] D. Steer, L. Fraser, J. Boddy, B. Seibert, Efficiency of small constructed wetlands for subsurface treatment of single-family domestic effluent, Ecological Engineering 18 (2002) 429-440. https://doi.org/10.1016/S0925-8574(01)00104-5. [21] J. Vymazal, The use of subsurface constructed wetlands for wastewater in Czech Republic: 10 years experience, Ecological Engineering 18 (2002) 633-646. https://doi.org/10.1016/S0925-8574(02)00025-3. [22] C.S. Akratos, V.A. Tsihrintzis, Effect of temperature, HRT, vegetation and porous media on removal efficiency of pilot-scale horizontal subsurface flow constructed wetlands, Ecological Engineering 29 (2007) 173-191. https://doi.org/ 10.1016/j.ecoleng.2006.06.013.